Adab as an Epistemological Paradigm in Islamic Education: Reexamining KH. Hasyim Asy’ari’s Thought in Adab al Alim wa al-Muta‘allim - Umu Kurnia Nurhidayah; Haris Supratno (Journal Of Islamic Education And Pesantren, 2023)
This study examines the concept of adab as an epistemological paradigm in Islamic education through a reexamination of the educational thought of KH. Hasyim Asy'ari in the classical work Adab al-‘Ālim wa al-Muta‘allim. The research departs from the assumption that adab in Islamic intellectual tradition is not merely a moral guideline regulating the behavior of teachers and students, but also constitutes a foundational principle that shapes the process of knowledge acquisition and the ethical orientation of learning. This study employs a qualitative library research approach using content analysis to explore the epistemological structure of adab in the text. The findings indicate that the paradigm of adab in KH. Hasyim Asy’ari’s educational thought is constructed through several interrelated dimensions: the purification of intention (niyyah) in seeking knowledge, ethical relationships between teachers and students, discipline in the learning process, and moral responsibility in the use of knowledge. These dimensions demonstrate that knowledge in Islamic education is inseparable from ethical formation and spiritual awareness. The study concludes that adab functions as an epistemological foundation that integrates intellectual development with moral cultivation, thereby offering a holistic framework for contemporary Islamic education.